Muscle activity during diaphragmatic breathing compared to abdominal crunches : a pilot study - Mohd. Hashim, Asha Hasnimy; Zainuddin, Zainal Abidin; Ibrahim, Halijah (2006)
The major barriers most people face when trying to increase physical activity are time, access to convenient facilities, and safe environments in which to be active. Therefore, other form of activity that can promote physical activity and strength are important due to it may protect against disability enhance functional independence and encourage regular physical activity participation. As a results, the diaphragmatic breathing is been introduced by researcher as another form of exercise that can meet the need of population for their abdominal strength. Diaphragmatic breathing is known as the most efficient breathing compared to others because of a greater expansion and ventilation occurs in the lower part of lung where the blood perfusion is greatest (Petrofsky et. al, 2005). During a forceful diaphragmatic breathing, a substantial abdominal muscle activity might be demonstrated. The purpose of this pilot study was to observed muscle activity during diaphragmatic breathing and abdominal crunches. This result then will be compare to determined which activity have greater total work on the abdominal muscles (rectus abdominis). With this result, we might suggest the effectiveness of diaphragmatic breathing towards abdominal muscle (rectus abdominis).